ECTHR_COMMITTEE 603/09 vom 24. Oktober 2017 , AFFAIRE BAYAR c. TURQUIE - Ecthr Committee (2017)
Violation de l'article 10 - Liberté d'expression-{général} (Article 10-1 - Liberté d'expression); Violation: 10;10-1